Wayang Beber sebagai Sarana Kritik Sosial - Aorta, Dian Tias; Prahastiwi, Eka Danik (Lembaga Yasin AlSys, 2025)
Wayang Beber is one of the cultural heritages of Nusantara that functions not only as a performative medium, but also as a space for expressing values, collective memory, and social criticism. This study aims to examine Wayang Beber as a medium of social criticism that reflects the realities of community life, particularly in the context of social change, power relations, and cultural dynamics. The research employs a qualitative approach with a descriptive–analytical method through literature study, performance observation, and visual and narrative analysis of Wayang Beber story fragments. The findings show that Wayang Beber contains visual symbols and narrative structures that serve as a medium of critique against social inequality, the degradation of human values, and power relations within society. Such criticism is conveyed symbolically, satirically, and reflectively, enabling it to be accepted across generations without losing its depth of meaning. This study affirms that Wayang Beber cannot be understood merely as a cultural artefact of the past, but rather as a form of cultural education and a living medium of social criticism that links tradition with contemporary realities and functions as a vehicle of cultural resistance against the homogenization of modernity. Accordingly, Wayang Beber has strategic potential as a space for social dialogue and critical reflection in cultural development and the strengthening of public awareness.